Selective photoredox decarboxylation of α-ketoacids to allylic ketones and 1,4-dicarbonyl compounds dependent on cobaloxime catalysis - Zhang, Hong; Xiao, Qian; Qi, Xu-Kuan; Gao, Xue-Wang; Tong, Qing-Xiao; Zhong, Jian-Ji (Chemical communications (Cambridge, England), 2020)
A photoredox/cobaloxime co-catalyzed coupling reaction of α-ketoacids and methacrylates to obtain allylic ketones is described. Without the cobaloxime catalyst, 1,4-dicarbonyl compounds are generated. The cobaloxime catalyst enables dehydrogenation to generate the formation of new olefins. The generality, good substrate scope and mild conditions are good features in the photoredox/cobaloxime catalysis protocol, and this method will provide new opportunities for the functionalization of more olefins. The selective synthesis of allylic ketones and 1,4-dicarbonyl compounds by photoredox/cobaloxime co-catalysis and photoredox catalysis, respectively, is described herein.